Rock climbing and raven Corvus corax occurrence depress breeding success of cliff-nesting peregrines Falco peregrinus - M. Brambilla; D. Rubolini; F. Guidali (Sociedad Española de Ornitologia, 2004)
Aims: To assess the significance of rock climbing-induced disturbance and Raven Corvus corax occurrence on the breeding output of a cliff-nesting Peregrine Falco peregrinus population. Location: Northern Italy- southern Switzerland. Methods: Breeding success, productivity and fledgling rate of 29 Peregrine pairs were analysed in relation to the occurrence of rock climbing activities and Ravens at nesting cliffs. Results: Breeding success and productivity were lower for pairs coexisting alternatively with Ravens or climbers, compared to undisturbed pairs. In addition, pairs settled at cliffs simultaneously occupied by Ravens and frequented by climbers did not fledge any young, suggesting that Raven predation on Peregrine eggs/chicks may be predisposed by human disturbance. Conclusion: It is proposed that rock climbing should be regulated or banned in the proximity of Peregrine nests, in particular at sites hosting Ravens.